2015
DOI: 10.15640/jea.v3n2a9
|View full text |Cite
|
Sign up to set email alerts
|

Creation of zero CO2 Emissions Hospitals Due to Energy Use A Case Study in Crete-Greece

Abstract: Hospitals consume a lot of energy for various operations compared with other buildings. They have complex energy systems and use conventional energy sources, mainly electricity, heating oil and natural gas. However various renewable energies can be used in order to cover their energy requirements resulting in low or zero CO2 emissions from them. Solar energy, solid biomass and geothermal energy can be used for that generating electricity, heat and cooling. A case study of a hospital in Crete-Greece proves that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 11 publications
0
15
0
Order By: Relevance
“…A profitability analysis of a 60 MW DC network for 1200 equivalent full load hours and cold water cost at 80 €/MWh shows that the a DC network is economically viable. Vourdoubas [11] has reported on the creation of zero carbon emissions hotels in Crete, Greece.…”
Section: Thus Countries With Large District Heating Sectors Like Denmmentioning
confidence: 99%
“…A profitability analysis of a 60 MW DC network for 1200 equivalent full load hours and cold water cost at 80 €/MWh shows that the a DC network is economically viable. Vourdoubas [11] has reported on the creation of zero carbon emissions hotels in Crete, Greece.…”
Section: Thus Countries With Large District Heating Sectors Like Denmmentioning
confidence: 99%
“…For the following estimations, it has been assumed that the embodied energy in the residential building with a life span of 50 years is equal to 15% of its life cycle (Vourdoubas, 2016).…”
Section: Estimation Of the Required Solar-pv System In Order To Zero mentioning
confidence: 99%
“…The highest potential in developed countries and economies in transition results from fuel savings. Vourdoubas, 2015 andVourdoubas, 2016 presented the possibility of creating zero-CO 2 emissions hotels and residential buildings due to energy use in Crete, Greece. The author indicated that two combinations of renewable energy technologies could cover all the energy needs of the buildings zeroing their CO 2 emissions in Crete.…”
Section: Sartori Et Al 2012mentioning
confidence: 99%